Dynamics of Insect–Microbiome Interaction Influence Host and Microbial Symbiont - Gupta, Ayushi; Nair, Suresh (Frontiers in Microbiology, 2020)
Insects share an intimate relationship with their gut microflora and this symbiotic association has developed into an essential evolutionary outcome intended for their survival through extreme environmental conditions. While it has been clearly established that insects, with very few exceptions, associate with several microbes during their life cycle, information regarding several aspects of these associations is yet to be fully unraveled. Acquisition of bacteria by insects marks the onset of microbial symbiosis, which is followed by the adaptation of these bacterial species to the gut environment for prolonged sustenance and successful transmission across generations. Although several insect-microbiome associations have been reported and each with their distinctive features, diversifications and specializations, it is still unclear as to what led to these diversifications. Recent studies have indicated the involvement of various evolutionary processes operating within an insect body that govern the transition of a free-living microbe to an obligate or facultative symbiont and eventually leading to the establishment and diversification of these symbiotic relationships. Data from various studies, summarized in this review, indicate that the symbiotic partners i.e. the bacteria and the insect undergo several genetic, biochemical and physiological changes that have profound influence on their life cycle and biology. An interesting outcome of the insect-microbe interaction is the compliance of the microbial partner to its eventual genome reduction. Endosymbionts possess a smaller genome as compared to their free-living forms, and thus raising the question what is leading to reductive evolution in the microbial partner? This review attempts to highlight the fate of microbes within an insect body and its implications for both the bacteria and its insect host. While discussion on each specific association would be too voluminous and outside the scope of this review, we present an overview of some recent studies that contribute to a better understanding of the evolutionary trajectory and dynamics of the insect-microbe association and speculate that, in the future, a better understanding of the nature of this interaction could pave the path to a sustainable and environmentally safe way for controlling economically important pests of crop plants.